Performance of Ultrasound in the Diagnosis of Gout in a Multicenter Study: Comparison With Monosodium Urate Monohydrate Crystal Analysis as the Gold Standard. Issue 2 (February 2017) - Ogdie, Alexis; Taylor, William J.; Neogi, Tuhina; Fransen, Jaap; Jansen, Tim L.; Schumacher, H. Ralph; Louthrenoo, Worawit; Vazquez‐Mellado, Janitzia; Eliseev, Maxim; McCarthy, Geraldine; Stamp, Lisa K.; Perez‐Ruiz, Fernando; et al.
Abstract : Objective: To examine the performance of ultrasound (US) for the diagnosis of gout using the presence of monosodium urate monohydrate (MSU) crystals as the gold standard. Methods: We analyzed data from the Study for Updated Gout Classification Criteria (SUGAR), a large, multicenter observational cross‐sectional study of consecutive subjects with at least 1 swollen joint who conceivably may have gout. All subjects underwent arthrocentesis; cases were subjects with confirmed MSU crystals. Rheumatologists or radiologists who were blinded with regard to the results of the MSU crystal analysis performed US on 1 or more clinically affected joints. US findings of interest were double contour sign, tophus, and snowstorm appearance. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. Multivariable logistic regression models were used to examine factors associated with positive US results among subjects with gout. Results: US was performed in 824 subjects (416 cases and 408 controls). The sensitivity, specificity, PPV, and NPV for the presence of any 1 of the features were 76.9%, 84.3%, 83.3%, and 78.2%, respectively. Sensitivity was higher among subjects with a disease duration of ≥2 years and among subjects with subcutaneous nodules on examination (suspected tophus). Associations with a positive US finding included suspected clinical tophus (odds ratio [OR] 4.77 [95% confidence interval (95% CI) 2.23–10.21]), any abnormality on plain radiography (OR 4.68 [95% CI 2.68–8.17]), and serum urate level (OR 1.31 [95% CI 1.06–1.62]). Conclusion: US features of MSU crystal deposition had high specificity and high PPV but more limited sensitivity for early gout. The specificity remained high in subjects with early disease and without clinical signs of tophi.